2014
DOI: 10.1164/rccm.201404-0744oc
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced Deoxycytidine Kinase Contributes to Epithelial Proliferation in Pulmonary Fibrosis

Abstract: Rationale: Idiopathic pulmonary fibrosis (IPF) is a deadly lung disease with few therapeutic options. Apoptosis of alveolar epithelial cells, followed by abnormal tissue repair characterized by hyperplastic epithelial cell formation, is a pathogenic process that contributes to the progression of pulmonary fibrosis. However, the signaling pathways responsible for increased proliferation of epithelial cells remain poorly understood.Objectives: To investigate the role of deoxycytidine kinase (DCK), an important e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 44 publications
(58 reference statements)
4
35
0
Order By: Relevance
“…Dck encodes deoxycytidine kinase which catalyzes phosphorylation of all four deoxynucleosides - essential for DNA replication. One recent study showed DCK plays a key role in cell proliferation30. Hist1h2a and Hist1h2b belong to histone cluster 1, the major histone gene locus also essential for DNA replication31.…”
Section: Resultsmentioning
confidence: 99%
“…Dck encodes deoxycytidine kinase which catalyzes phosphorylation of all four deoxynucleosides - essential for DNA replication. One recent study showed DCK plays a key role in cell proliferation30. Hist1h2a and Hist1h2b belong to histone cluster 1, the major histone gene locus also essential for DNA replication31.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that other pathologic phenotypes of myo-Fbs, such as augmented proliferation and resistance to apoptosis, could be also dependent on the elevated glycolysis. In addition, highly glycolytic myo-Fbs may be capable of creating a metabolically favorable microenvironment through secreting lactate and other glycolytic intermediates to cause pathologic changes in adjacent pulmonary cells, such as cellular dysplasia, which is frequently found in the alveolar epithelia surrounding the myofibroblastic foci in IPF lungs (52). Although these hypotheses remain to be tested, there is abundant evidence alluding that such events could take place during pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The lungs of IPF patients are often characterized by the presence of fibroblastic foci surrounded by hyperplastic type II alveolar epithelial cells (AEC2s), 10 which become hypoxic and express increased levels of hypoxia-inducible factor-1 α (HIF-1 α ). 11 Further, large-scale genomic studies on lungs of IPF patients indicate that hypoxia signaling likely drives profibrotic events in IPF.…”
Section: Introductionmentioning
confidence: 99%